Comparative Study On The Effect Of Some Parameters On The Behavior Of R.C.C And Composite Columns Under Pushover Loading - طوالو, علي (Latakia University Journal -Engineering Sciences Series, 2025)
The use of steel columns with hollow cross-sections filled with concrete is one of the effective techniques in high-rise composite buildings, as it relies on the principle of sharing between two materials working together in one structural element while taking the advantages of each material, like the tensile strength of steel and pressure of concrete. In this research, the effect of some parameters on the seismic behavior of twenty composite columns specimens subjected to Pushover loading applied at the top of the column was studied. The selected parameters were: the varying thickness/width ratio of the steel element, the axial compression ratio of the column, and the yield stress values ​​used for steel elements. Through the results of the research and based on the results of some practical experiments in the references, it was found that the use of composite elements contributes to increasing the bearing capacity of the element and reducing its dimensions, which is positively reflected on the self-weight and seismic forces in addition to reducing the construction cost.